A Technological History of Cold-War India, 1947–⁠1969 - Logan, William A.T. author. aut Link
XVIII, 282 p. 27 illus., 8 illus. in color.
Keywords: ‘This well-written book provides an insightful and succinct “technological history” of development in early post-independence India under the challenges posed by the Cold War. This nuanced study, drawing on a wide range of materials, persuasively discusses how autarky as practiced with reference to technological indigenization conflicted with the economic and political realities of the Cold War world. Indeed, for those interested in better understanding the India of today, in particular, the changes in the Indian economy, this book provides much food for thought. An important addition to South Asian and India studies.’ --Sharma Shalendra, Lingan University This book provides a technological history of modern India, in particular the Nehruvian development in the context of the Cold War. Through a series of case studies about military modernization, transportation infrastructure, and electric power, it examines how the ideals of autarky and technological indigenization conflicted with the economic and political realities of the Cold War world. Where other studies tend to focus on the political leaders and economists who oversaw development, this book demonstrates how the perspective of the engineers, government bureaucrats, and aid workers informed and ultimately implemented development. William A.T. Logan is Assistant Professor of History at Pacific Union College, USA.